Insights into disability and psycho-social care of patients with inflammatory bowel disease - Nardone, Olga Maria; Calabrese, Giulio; La Mantia, Alessia; Caso, Rossella; Testa, Anna; Castiglione, Fabiana (Frontiers in Medicine, 2024)
In recent years, the concept of disability has increasingly garnered attention as a crucial long-term target of inflammatory bowel disease (IBD) management. The treatment paradigm has changed dramatically from full control of the disease (clinical and endoscopic remission) toward physical and emotional well-being with the goal of preventing disability and normalizing quality of life. However, in certain cases, despite achieving good disease control, patients may still experience symptoms associated with disability, and reduced emotional wellness. These symptoms can significantly impact various biopsychosocial factors, including interpersonal relationships, educational or work-related activities, body image, and sexual functioning. Nevertheless, they often remain overlooked in the context of IBD care. In this narrative review, we aim to shed light on the burden of certain disability-related symptoms such as bowel urgency, sexual dysfunction, impaired fertility and fatigue, emphasizing the importance of acknowledging and validating them in a clinical setting. There is a demanding need for comprehensive care for IBD patients, with IBD clinicians being mindful of the psychosocial challenges faced by their patients. Providing timely and appropriate management of these challenges alongside IBD treatment is key to achieving holistic remission and enhancing the overall quality of life while reducing disability.